Percutaneous pulmonary valve replacement in a large right ventricular outflow tract: an experimental study - Boudjemline, Younes; Agnoletti, Gabriella; Bonnet, Damien; Sidi, Daniel; Bonhoeffer, Philipp (Journal of the American College of Cardiology, 2004)
We report our initial experience with percutaneous pulmonary valve replacement in animals with large pulmonary trunks, using a modified percutaneous approach. Percutaneous pulmonary valve replacement has recently been introduced, and early clinical experience has been reported. This technique is presently limited to patients with a right ventricular outflow tract no bigger than 22 mm in diameter. In seven animals (groups 1 and 3), we implanted a newly designed nitinol stent in the shape of a conduit with a central restriction of its diameter, containing an 18-mm bovine valve, as a one-step procedure. The animals in groups 1 and 3 were sacrificed after valve implantation and after two-month follow-up, respectively. In the second group (n = 3), we expected to percutaneously reduce the diameter of the pulmonary artery. Eight weeks later, we implanted an 18-mm valve mounted in a balloon-expandable stent. These animals were sacrificed after valve implantation. Eight of 10 devices were successfully delivered and were functioning perfectly at the initial evaluation and after two months. We failed to cross the tricuspid valve in two cases. The downsize mechanism allowed the pulmonary diameter to be reduced from 30 to 18 mm, without an impact on right ventricular function in any of the animals. Non-surgical implantation of a pulmonary valve is possible in ewes with all types of pulmonary trunk, regardless of its size. A "downsize" stent is needed to allow valve implantation in a large trunk. Further refinements will make this technique feasible in humans.